Multi-discipline and multi-grade lessons in the study of Dactylopius (Homoptera: Coccoidea: Dactylopiidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The Dactylopius (cochineal) insect has been used as a source of red dye for over three thousand years, however there is lirnited public knowledge of it. As entomologists leave the profession, the need for new entomologists increases, especially in light of the continuing shortage of professionals. To bridge that gap, educational activities that attract, inspire, and encourage people, especially young students, are discussed. Included are cross-curricular cochineal activities that involve multi-level students, in both the classroom and community.
Keywords: Opuntia; cochineal; carrninic acid; education; publishing